Overcoming coordination gaps between water, energy and agriculture: Future paths to water protection in Weser-Ems - Franziska Meergans; Christina Aue; Christian Knieper; Sascha Kochendörfer; Andrea Lenschow; Claudia Pahl-Wostl (Deutsches Institut für Entwicklungspolitik (DIE), 2020)
This paper constitutes one of six analyses of cross-sectoral challenges in water governance. These have been conducted as part of the STEER research project and results are published in separate analyses and position papers. While the agricultural sector and food industry of the region of Weser-Ems in Lower Saxony have brought about economic prosperity, they have also posed challenges to the environment, and water quality in particular. Intensive animal farming is considered the main source of nitrate pollution in groundwater, a trend that has been further reinforced by the promotion of non-fossil fuel energy sources and increased biogas production in the region. Against this backdrop, coordination of the water, (bio)energy and agricultural sectors is key to establishing Integrated Water Resources Management (IWRM) in the region and thereby reducing nitrate levels in the groundwater. This paper is based on the analysis of coordination and cooperation among local and regional stakeholders which takes account of i) legal and regulatory structures, ii) water management processes and iii) the socio-ecological conditions. It shows that groundwater protection in the region of Weser-Ems has for two decades been characterised by the same trade-off between the barely coordinated policies of the water, (bio)energy and agricultural sectors. The problem thus remains as pressing as ever. The lack of sufficient coordination between Germany's Renewable Energy Act (EGG) and its Fertiliser Ordinance (DüV) is inconsistent with growing international recognition of the need for coherent and integrated policy solutions to the management of natural resources such as groundwater. For many years, the German agricultural policy, of central importance for water resources management, was geared solely to profitability in agriculture, neglecting the considerable social and environmental costs of this approach. It is not yet possible to gauge the extent to which the amendment of the Fertiliser Ordinance in 2020 and the designation of nitrate vulnerable zones have led to effective integration. In order to reduce nitrate pollution in the region of Weser-Ems and similar regions of Germany in the long term, we make the following recommendations in this paper: * improve legislative coordination in the water, energy and agricultural sectors, * expand and promote successful (local) projects (e.g. whole-farm approach), * transform intensive farming into business models combining profitability with ecological compatibility (e.g. organic farming), * support this by integrating practical knowledge into the development of new policy instruments, and * elevate water protection issues in agricultural training.
Keywords: 330